Rolled copper foil surface treatment method, high-corrosion-resistance rolled copper foil and application of high-corrosion-resistance rolled copper foil
By performing multiple surface treatment on the rolled copper foil to form an alloy plating layer, the problem of insufficient corrosion resistance of the rolled copper foil in traditional processes is solved, and the anti-side corrosion effect during etching and the application requirements of fine line width-distance printed circuit boards are achieved.
Patent Information
- Application Number
- CN202510052362.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
AI Technical Summary
The traditional surface treatment process of rolled copper foil has poor corrosion resistance, which is prone to side corrosion problems during etching, and cannot meet the requirements of fine line width-distance printed circuit boards.
By adopting a comprehensive method of pickling treatment, roughening treatment, curing treatment, alloying treatment, anti-oxidation treatment and passivation treatment, a uniform and dense alloy coating is formed on the surface of the rolled copper foil, the amount of plating of the plated metal ions is improved and its corrosion resistance is enhanced.
It effectively improves the anti-lateral corrosion ability of the rolled copper foil, ensures that the side corrosion phenomenon is not prone to occur during the etching process, and avoids etching residues, meeting the preparation needs of fine line width distance printed circuit boards.
Smart Images

Figure CN119843333A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper foil surface treatment, and in particular to a surface treatment method for a rolled copper foil, a highly corrosion-resistant rolled copper foil and applications thereof. Background Art
[0002] Rolled copper foil is a key material for manufacturing high-end electronic products such as printed circuit boards (PCBs). It is a foil product made from high-purity copper by rolling. Rolled copper foil has better folding resistance, strength, softening temperature and lower surface roughness. However, rolled copper foil is easily oxidized in the air and its surface is easily corroded, which in turn affects its conductivity, surface roughness and color, greatly limiting its application. Therefore, rolled copper foil needs to be surface treated before being pressed with an insulating substrate to manufacture a PCB board. The quality of the surface treatment process directly determines the superiority of its anti-peel strength, anti-side corrosion, anti-oxidation and other properties.
[0003] When preparing PCB boards with rolled copper foil, the required circuit pattern needs to be obtained through etching. With the rapid development of PCB technology, the rapid iteration and upgrading of electronic products and the diversification of application scenarios, PCB has tended to be high-frequency, high-speed and high-density, and higher requirements have been put forward for the circuit level of circuit boards. The line width has gradually developed from 100μm to a more refined direction. It has now developed from 75μm lines to 50μm lines and even 30μm fine lines. However, the corrosion resistance of rolled copper foil treated by traditional surface treatment technology is poor, and side etching problems will inevitably occur during etching, that is, side etching of the line will occur when etching to remove the copper layer, which will affect signal transmission and cannot meet the requirements of fine line width printed circuit boards. Summary of the invention
[0004] In view of this, the present invention provides a surface treatment method for rolled copper foil, a highly corrosion-resistant rolled copper foil and its application. The surface treatment method provided by the present invention can improve the side corrosion resistance of the rolled copper foil, and the rolled copper foil treated by the surface treatment method of the present invention will not have side corrosion problems during etching, and can meet the requirements of fine line width printed circuit boards.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] A method for surface treatment of rolled copper foil comprises the following steps:
[0007] The rolled copper foil is sequentially subjected to pickling treatment, roughening treatment, curing treatment, alloying treatment, anti-oxidation treatment and passivation treatment to obtain a highly corrosion-resistant rolled copper foil;
[0008] The roughening liquid used in the roughening treatment includes copper ions and sulfuric acid;
[0009] The curing liquid used in the curing treatment includes copper ions and sulfuric acid;
[0010] The total content of soluble sulfate in the alloying solution used for the alloying treatment is 30-100 g / L, and the content of the complexing agent is 20-120 g / L; the soluble sulfate in the alloying solution includes nickel sulfate; the content of nickel ions in the surface coating of the high corrosion-resistant rolled copper foil is 1500-2000 μg / dm 2 ;
[0011] The anti-oxidation liquid used in the anti-oxidation treatment includes chromium ions, zinc ions and potassium pyrophosphate;
[0012] The passivation agent used in the passivation treatment is a coupling agent solution.
[0013] Preferably, the alloying treatment temperature is 25-30°C and the current density is 5-15A / dm 2 , pH value is 8-10, and electroplating time is 3-5s.
[0014] Preferably, the soluble sulfate in the alloying solution further includes one or more of copper sulfate, titanium sulfate and cerium sulfate.
[0015] Preferably, the complexing agent is an organic substance having a carboxyl group and / or an amino group.
[0016] Preferably, the complexing agent comprises one or more of glycolic acid, citric acid, ammonium citrate, thiourea, glycine, phenylalanine, glutamic acid, histidine and alanine.
[0017] Preferably, the concentration of copper ions in the roughening solution used in the roughening treatment is 5-15 g / L, and the concentration of sulfuric acid is 80-130 g / L; the temperature of the roughening treatment is 25-35 ° C, and the current density is 18-30 A / dm 2 , the electroplating time is 5 to 10 seconds.
[0018] Preferably, the concentration of copper ions in the curing liquid used for the curing treatment is 20-60 g / L, and the concentration of sulfuric acid is 80-130 g / L; the temperature of the curing treatment is 25-35°C, and the current density is 10-15 A / dm 2 , the electroplating time is 3 to 6s.
[0019] Preferably, the concentration of chromium ions in the anti-oxidation solution used for the anti-oxidation treatment is 0.5-1 g / L, the concentration of zinc ions is 2-4 g / L, and the concentration of potassium pyrophosphate is 100-200 g / L; the pH value of the anti-oxidation solution is 11-12; the temperature of the anti-oxidation treatment is 20-30°C, and the current density is 2-10 A / dm 2 , the processing time is 5 to 10 seconds;
[0020] The passivation treatment is to spray a coupling agent solution onto the surface of the rolled copper foil after the anti-oxidation treatment; the volume concentration of the coupling agent solution is 1-2%.
[0021] The present invention also provides a highly corrosion-resistant rolled copper foil, which is obtained by subjecting the rolled copper foil to surface treatment, wherein the surface treatment method is the surface treatment method described in the above scheme.
[0022] The present invention also provides the use of the high corrosion-resistant rolled copper foil described in the above scheme in the preparation of a fine line width printed circuit board; the line width of the fine line width printed circuit board is less than 50 μm.
[0023] The invention provides a surface treatment method for a rolled copper foil, comprising the following steps: sequentially subjecting the rolled copper foil to pickling treatment, roughening treatment, curing treatment, alloying treatment, anti-oxidation treatment and passivation treatment to obtain a high-corrosion-resistant rolled copper foil; the roughening solution used in the roughening treatment comprises copper ions and sulfuric acid; the curing solution used in the curing treatment comprises copper ions and sulfuric acid; the total content of soluble sulfate in the alloying solution used in the alloying treatment is 30-100 g / L, and the content of a complexing agent is 20-120 g / L; the soluble sulfate in the alloying solution comprises nickel sulfate; the content of nickel ions in the surface plating layer of the high-corrosion-resistant rolled copper foil is 1500-2000 μg / dm 2 ; The anti-oxidation liquid used in the anti-oxidation treatment includes chromium ions, zinc ions and potassium pyrophosphate; the passivation agent used in the passivation treatment is a coupling agent solution. The present invention adds a complexing agent to the alloying liquid used for the alloying treatment, and forms a uniform and dense alloy coating on the surface of the copper foil through the action of the complexing agent, thereby increasing the amount of metal ions plated on the coating, and improving the corrosion resistance of the rolled copper foil, thereby reducing the circuit side corrosion caused when the copper layer is etched away; and the present invention controls the content range of nickel ions in the high corrosion-resistant rolled copper foil coating obtained after the surface treatment, so as to ensure that the high corrosion-resistant rolled copper foil obtained is not prone to side corrosion during the etching process, and no etching residue will occur. In summary, the rolled copper foil surface-treated according to the method of the present invention has good anti-side corrosion ability, and can better meet the preparation requirements of printed circuit boards with a line width and line spacing of less than 50μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of copper foil without side etching (top) and copper foil with side etching (bottom). DETAILED DESCRIPTION
[0025] The present invention provides a method for surface treatment of rolled copper foil, comprising the following steps:
[0026] The rolled copper foil is sequentially subjected to pickling treatment, roughening treatment, curing treatment, alloying treatment, anti-oxidation treatment and passivation treatment to obtain a high corrosion resistant rolled copper foil; the total content of soluble sulfate in the alloying solution used for the alloying treatment is 30-100 g / L, and the content of the complexing agent is 20-120 g / L; the soluble sulfate in the alloying solution includes nickel sulfate; the content of nickel ions in the surface coating of the high corrosion resistant rolled copper foil is 1500-2000 μg / dm 2 .
[0027] The present invention performs pickling treatment on the rolled copper foil. In the present invention, the pickling solution used in the pickling treatment is preferably a sulfuric acid solution, and the concentration of the sulfuric acid solution is preferably 10wt%; the present invention has no special requirements for the specific conditions of the pickling, and those familiar to those skilled in the art can be used; after pickling, the rolled copper foil is preferably cleaned with deionized water.
[0028] After the pickling treatment is completed, the present invention performs a roughening treatment on the rolled copper foil after the pickling treatment. In the present invention, the concentration of copper ions in the roughening solution used for the roughening treatment is preferably 5-15 g / L, and the concentration of sulfuric acid is preferably 80-130 g / L, specifically 100 g / L, 110 g / L or 120 g / L; in a specific embodiment of the present invention, the roughening solution is prepared from copper sulfate pentahydrate, sulfuric acid and water; the temperature of the roughening treatment is preferably 25-35°C, specifically 25°C, 30°C or 35°C; the current density of the roughening treatment is preferably 18-30 A / dm 2 , specifically 18A / dm 2 、20A / dm 2 or 25A / dm 2 The electroplating time of the roughening treatment is preferably 5 to 10 seconds, specifically 6 seconds, 8 seconds or 9 seconds. The present invention performs roughening treatment under the above conditions, which can deposit fine copper powder on the surface of the copper foil, improve the roughness of the copper foil surface, and increase the active sites on the copper foil surface.
[0029] After the roughening treatment is completed, the present invention performs a curing treatment on the rolled copper foil after the roughening treatment. In the present invention, the concentration of copper ions in the curing liquid used for the curing treatment is preferably 20-60 g / L, and the concentration of sulfuric acid is preferably 80-130 g / L, specifically 90 g / L, 110 g / L or 120 g / L; in a specific embodiment of the present invention, the curing liquid is prepared from copper sulfate pentahydrate, sulfuric acid and water; the temperature of the curing treatment is preferably 25-35°C, specifically 25°C, 30°C or 35°C; the current density of the curing treatment is preferably 10-15 A / dm 2 , specifically 10A / dm 2 、12A / dm 2 or 15A / dm2 The electroplating time of the curing treatment is preferably 3 to 6 seconds, specifically 3 seconds, 4 seconds or 5 seconds. The present invention deposits a layer of copper on the surface of the roughened copper foil through the curing treatment to prevent the copper powder from falling off.
[0030] After the curing treatment is completed, the present invention performs alloying treatment on the rolled copper foil after the curing treatment. In the present invention, the alloying solution used for the alloying treatment includes soluble sulfate, complexing agent and water; the total content of soluble sulfate in the alloying treatment solution is 30-100 g / L, specifically 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L or 90 g / L, the soluble sulfate includes nickel sulfate, preferably also includes one or more of copper sulfate, titanium sulfate and cerium sulfate, the nickel sulfate is specifically nickel sulfate heptahydrate, and the copper sulfate is specifically copper sulfate pentahydrate.
[0031] In one or more specific embodiments of the present invention, the soluble sulfate in the alloying solution preferably includes nickel sulfate and copper sulfate at the same time, wherein the concentration of nickel sulfate is preferably 30-50 g / L, specifically 30 g / L, 32 g / L, 34 g / L, 36 g / L, 40 g / L, 45 g / L or 50 g / L, and the concentration of copper sulfate is preferably 3-32 g / L, specifically 3 g / L, 5 g / L, 8 g / L, 10 g / L, 12 g / L, 13 g / L or 32 g / L.
[0032] In other specific embodiments of the present invention, the soluble sulfate in the alloying solution preferably includes nickel sulfate, copper sulfate and auxiliary sulfate at the same time, and the auxiliary sulfate is one or more of titanium sulfate and cerium sulfate, wherein the concentration of nickel sulfate is preferably 30-50 g / L, specifically 30 g / L, 32 g / L, 34 g / L, 36 g / L, 40 g / L, 45 g / L or 50 g / L, the concentration of copper sulfate is preferably 3-32 g / L, specifically 3 g / L, 5 g / L, 8 g / L, 10 g / L, 12 g / L, 13 g / L or 32 g / L, and the concentration of auxiliary sulfate is preferably 0.1-1.5 g / L, specifically 0.5 g / L, 0.8 g / L, 1 g / L or 1.5 g / L.
[0033] In the present invention, the content of the complexing agent in the alloying solution is preferably 20-120 g / L, specifically 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L or 110 g / L; the complexing agent is preferably an organic matter with a carboxyl group and / or an amino group, specifically, the complexing agent preferably includes one or more of glycolic acid, citric acid, ammonium citrate, thiourea, glycine, phenylalanine, glutamic acid, histidine and alanine; in a specific embodiment of the present invention, the complexing agent can be a mixture of glycolic acid and thiourea, or a mixture of citric acid and phenylalanine.
[0034] In the present invention, the temperature of the alloying treatment is preferably 25 to 30°C, specifically 25°C, 30°C or 35°C, and the current density is preferably 5 to 15A / dm 2 , specifically 8A / dm 2 、10A / dm 2 or 12A / dm 2 The pH value is preferably 8 to 10, specifically 8.5, 9, 9.5 or 10; in a specific embodiment of the present invention, sodium hydroxide is used to adjust the pH value of the alloying solution to the above range; the electroplating time of the alloying treatment is preferably 3 to 5s, specifically 3s, 4s or 5s.
[0035] After the alloying treatment is completed, the present invention performs an anti-oxidation treatment on the rolled copper foil after the alloying treatment. In the present invention, the concentration of chromium ions in the anti-oxidation solution used for the anti-oxidation treatment is preferably 0.5-1g / L, specifically 0.6g / L, 0.8g / L or 0.9g / L, the concentration of zinc ions is preferably 2-4g / L, specifically 2.5g / L, 3g / L or 4g / L, and the concentration of potassium pyrophosphate is preferably 100-200g / L, specifically 120g / L, 150g / L or 170g / L; the pH value of the anti-oxidation solution is preferably 11-12; in a specific embodiment of the present invention, the anti-oxidation solution is specifically prepared from soluble chromium salt, soluble zinc salt, potassium pyrophosphate and water; the present invention has no special requirements for the specific types of the soluble chromium salt and soluble zinc salt, and those familiar to those skilled in the art can be used.
[0036] In the present invention, the temperature of the anti-oxidation treatment is preferably 20-30°C, specifically 25°C, 30°C or 35°C, and the current density of the anti-oxidation treatment is preferably 2-10A / dm 2 , specifically 3A / dm 2 , 5A / dm 2 or 8A / dm 2The time of the anti-oxidation treatment is preferably 5 to 10 seconds, specifically 6 seconds, 8 seconds or 9 seconds. The present invention performs the anti-oxidation treatment under the above conditions, and can deposit an anti-oxidation layer on the surface of the copper foil, thereby improving the anti-oxidation ability of the copper foil.
[0037] After the anti-oxidation treatment is completed, the present invention performs a passivation treatment on the rolled copper foil after the anti-oxidation treatment. In the present invention, the passivation treatment is preferably spraying a coupling agent solution on the surface of the rolled copper foil after the anti-oxidation treatment; the volume concentration of the coupling agent solution is preferably 1-2%; the coupling agent in the coupling agent solution is preferably a silane coupling agent, more preferably an epoxy silane coupling agent; the present invention has no special requirements for the type of the silane coupling agent, and those familiar to those skilled in the art can be used, such as KH560.
[0038] In the present invention, the content of nickel ions in the surface plating layer of the high corrosion-resistant rolled copper foil obtained after the above surface treatment is 1500-2000 μg / dm 2 , preferably 1528~1995μg / dm 2 The present invention controls the content of nickel ions within the above range, which can ensure that the copper foil is not prone to side etching during the etching process and that no etching residue will occur.
[0039] The present invention also provides a highly corrosion-resistant rolled copper foil, which is obtained by surface treating the rolled copper foil, wherein the surface treatment method is the surface treatment method described in the above scheme; the content of nickel ions in the surface coating of the highly corrosion-resistant rolled copper foil is consistent with that in the above scheme, and will not be repeated here.
[0040] The present invention also provides the use of the high corrosion-resistant rolled copper foil described in the above scheme in the preparation of a fine line width printed circuit board; the line width of the fine line width printed circuit board is less than 50 μm.
[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1
[0043] This embodiment provides a method for surface treatment of rolled copper foil, and the specific steps are as follows:
[0044] Pickling treatment: Place the rolled copper foil in a dilute sulfuric acid pickling solution with a mass concentration of 10% for pickling, and then rinse with deionized water;
[0045] Roughening treatment: The cleaned rolled copper foil is roughened in a roughening solution with a copper ion concentration of 10 g / L and a sulfuric acid concentration of 100 g / L. The roughening temperature is 25°C and the current density is 18 A / dm 2 , the electroplating time is 8s;
[0046] Curing treatment: The rolled copper foil after roughening treatment is cured in a curing solution. The concentration of copper ions in the curing solution is 25g / L, the concentration of sulfuric acid is 110g / L, the curing temperature is 25℃, and the current density is 10A / dm 2 , the electroplating time is 3s;
[0047] Alloying treatment: The rolled copper foil after curing is placed in an alloying solution for electrodeposition. The concentration of nickel sulfate heptahydrate in the alloying solution is 32 g / L, the concentration of copper sulfate pentahydrate is 12 g / L, the concentration of ammonium citrate is 60 g / L, and the pH value is 9. The alloying temperature is 25°C and the current density is 10 A / dm 2 , the electroplating time is 3s;
[0048] Anti-oxidation treatment: The rolled copper foil after alloying treatment is subjected to anti-oxidation treatment in an anti-oxidation solution, wherein the concentration of chromium ions is 0.6 g / L, the concentration of zinc ions is 3 g / L, and the concentration of potassium pyrophosphate is 170 g / L; the pH value of the anti-oxidation solution is 11.2; the temperature of the anti-oxidation treatment is 25°C, and the current density is 5 A / dm 2 , the processing time is 6s;
[0049] Passivation treatment: Spray the anti-oxidation treated copper foil with a coupling agent solution, the volume concentration of the coupling agent solution is 1%, wherein the coupling agent solution used is an epoxy silane coupling agent (KH560) solution.
[0050] Example 2
[0051] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 40 g / L, the concentration of copper sulfate pentahydrate is 10 g / L, the concentration of ammonium citrate is 50 g / L, and the concentration of titanium sulfate is 0.8 g / L; the temperature of the alloying treatment is 25°C, the pH value is 9, and the current density is 8 A / dm 2 , the electroplating time is 5s;
[0052] The rest is the same as in Example 1.
[0053] Example 3
[0054] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 30 g / L, the concentration of copper sulfate pentahydrate is 32 g / L, the concentration of ammonium citrate is 45 g / L, and the concentration of cerium sulfate is 0.7 g / L; the temperature of the alloying treatment is 25°C, the pH value is 9, and the current density is 11 A / dm 2 , the electroplating time is 3s;
[0055] The rest is the same as in Example 1.
[0056] Example 4
[0057] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 34 g / L, the concentration of copper sulfate pentahydrate is 8 g / L, the concentration of ammonium citrate is 45 g / L, the concentration of titanium sulfate is 1 g / L, and the concentration of cerium sulfate is 1.5 g / L; pH = 9, the temperature current density of the alloying treatment is 10 A / dm 2 , electroplating time 4s;
[0058] The rest is the same as in Example 1.
[0059] Example 5
[0060] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 36 g / L, the concentration of copper sulfate pentahydrate is 5 g / L, the concentration of glycolic acid is 40 g / L, the concentration of thiourea is 5 g / L, the pH is 9, and the current density of the alloying treatment is 7 A / dm 2 , the electroplating time is 5s;
[0061] The rest is the same as in Example 1.
[0062] Example 6
[0063] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 40 g / L, the concentration of copper sulfate pentahydrate is 10 g / L, the concentration of citric acid is 30 g / L, the concentration of phenylalanine is 45 g / L, the pH is 9, and the current density of the alloying treatment is 9 A / dm 2 , the electroplating time is 3s;
[0064] The rest is the same as in Example 1.
[0065] Example 7
[0066] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 45 g / L, the concentration of copper sulfate pentahydrate is 10 g / L, the concentration of glutamic acid is 80 g / L, the pH is 9, and the current density of the alloying treatment is 10 A / dm 2 , the electroplating time is 3s;
[0067] The rest is the same as in Example 1.
[0068] Example 8
[0069] The difference between this embodiment and embodiment 1 is that in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 34 g / L, the concentration of copper sulfate pentahydrate is 8 g / L, the concentration of phenylalanine is 60 g / L, the pH is 9, and the current density of the alloying treatment is 10 A / dm 2 , the electroplating time is 3s.
[0070] The rest is the same as in Example 1.
[0071] Example 9
[0072] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 50 g / L, the concentration of copper sulfate pentahydrate is 13 g / L, the concentration of glycine is 50 g / L, the pH is 9, and the current density of the alloying treatment is 8 A / dm 2 , the electroplating time is 3s;
[0073] The rest is the same as in Example 1.
[0074] Example 10
[0075] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 28 g / L, the concentration of copper sulfate pentahydrate is 3 g / L, the concentration of histidine is 40 g / L, the pH is 9, and the current density of the alloying treatment is 12 A / dm 2 , the electroplating time is 3s;
[0076] The rest is the same as in Example 1.
[0077] Comparative Example 1
[0078] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 80 g / L, the concentration of copper sulfate pentahydrate is 20 g / L, the concentration of ammonium citrate is 50 g / L, the pH is 9, and the current density of the alloying treatment is 10 A / dm 2 , the electroplating time is 4s;
[0079] The rest is the same as in Example 1.
[0080] Comparative Example 2
[0081] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 20 g / L, the concentration of copper sulfate pentahydrate is 8 g / L, the concentration of ammonium citrate is 45 g / L, the pH is 9, and the current density of the alloying treatment is 10 A / dm 2, the electroplating time is 5s;
[0082] The rest is the same as in Example 1.
[0083] Comparative Example 3
[0084] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 30 g / L, the concentration of copper sulfate pentahydrate is 18 g / L, the concentration of ammonium citrate is 40 g / L, the pH is 9, and the current density of the alloying treatment is 10 A / dm 2 , the electroplating time is 3s;
[0085] The rest is the same as in Example 1.
[0086] Comparative Example 4
[0087] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 50 g / L, the concentration of copper sulfate pentahydrate is 12 g / L, the concentration of ammonium citrate is 60 g / L, the pH is 3, and the current density of the alloying treatment is 10 A / dm 2 , the electroplating time is 3s;
[0088] The rest is the same as in Example 1.
[0089] Comparative Example 5
[0090] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 40 g / L, the concentration of copper sulfate pentahydrate is 14 g / L, no complexing agent is added, pH=9, and the current density of the alloying treatment is 10 A / dm 2 , the electroplating time is 3s;
[0091] The rest is the same as in Example 1.
[0092] Comparative Example 6
[0093] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 40 g / L, the concentration of copper sulfate pentahydrate is 9 g / L, the concentration of thiourea is 70 g / L, the pH is 9, and the current density of the alloying treatment is 10 A / dm 2 , the electroplating time is 3s;
[0094] The rest is the same as in Example 1.
[0095] Comparative Example 7
[0096] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 32 g / L, the concentration of copper sulfate pentahydrate is 7 g / L, the concentration of citric acid is 30 g / L, the pH is 9, and the current density of the alloying treatment is 10 A / dm2 , the electroplating time is 3s;
[0097] The rest is the same as in Example 1.
[0098] Comparative Example 8
[0099] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 30 g / L, the concentration of copper sulfate pentahydrate is 6 g / L, the concentration of phenylalanine is 120 g / L, the pH is 9, and the current density of the alloying treatment is 10 A / dm 2 , the electroplating time is 3s;
[0100] The rest is the same as in Example 1.
[0101] Comparative Example 9
[0102] The difference between this embodiment and embodiment 1 is that: in step 4), the concentration of nickel sulfate heptahydrate in the alloying solution is 60 g / L, the concentration of copper sulfate pentahydrate is 6 g / L, no complexing agent is added, pH=2, and the current density of the alloying treatment is 3 A / dm 2 , the electroplating time is 3s;
[0103] The rest is the same as in Example 1.
[0104] Performance Testing
[0105] In order to more clearly describe the performance of the high corrosion-resistant copper foil obtained after the surface treatment of the present invention, the test method of the performance index involved in the present invention is introduced as follows:
[0106] Electrochemical workstation: The electrochemical workstation was used to test the Tafel curve to evaluate the corrosion resistance of the copper foil coating. The electrochemical test adopted a three-electrode system. The test experiment was carried out in a homemade electrolytic cell. The test solution was a 3.5wt% sodium chloride solution. The copper foil was the working electrode, the platinum electrode was the auxiliary electrode, and the saturated potassium chloride electrode was the reference electrode.
[0107] Etching test: Copper foil and epoxy resin semi-cured polyimide film are hot pressed into copper clad board by vacuum press, and then etched on the etching machine according to IPC-TM-650 method.
[0108] Coating content detection: cut 1dm 2 The copper foil was coated with a mixed acid (nitric acid: hydrochloric acid = 3:1) for dissolution, and digested with a microwave digester. The results were detected and analyzed with an inductively coupled plasma optical emission spectrometer (ICP-OES).
[0109] Side etching: Copper foil and epoxy resin semi-cured polyimide film are hot pressed into copper clad board by vacuum press, etched into 1mm lines on etching machine, micro-etched three times with 10wt% H2SO4 and 5wt% H2O2, and the line edge is observed by argon ion polishing-metallographic microscope. If the single-side micro-etching is ≤10μm, there is no side etching, and if it is greater than 10μm, there is side etching. Figure 1 The copper foil in the upper middle picture indicates no side etching, and the copper foil in the lower picture indicates side etching.
[0110] The test results are shown in Table 1.
[0111] Table 1 Test results
[0112]
[0113] From the results in Table 1, it can be seen that the rolled copper foil treated by the surface treatment method of the present invention has higher corrosion resistance, can reduce the side corrosion of the copper foil, and can be better applied to printed circuit boards with fine line widths; the corrosion potential and current of Experimental Example 4 are the smallest, which shows that it has the strongest corrosion resistance; the nickel content in Comparative Example 1 exceeds 2000 μg / dm 2 , the etching time increases, and etching residue is likely to occur; the nickel content of the coating in Comparative Examples 2 to 9 is less than 1500 μg / dm 2 In Comparative Example 9, no complexing agent was added to the alloying solution, and the alloying treatment was carried out under acidic conditions. The nickel ion content in the final coating was significantly reduced, the corrosion resistance was poor, and the side corrosion phenomenon was prone to occur.
[0114] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for surface treatment of rolled copper foil, characterized in that: The following steps are involved: The rolled copper foil is sequentially subjected to pickling treatment, roughening treatment, curing treatment, alloying treatment, anti-oxidation treatment and passivation treatment to obtain a highly corrosion-resistant rolled copper foil; The roughening liquid used in the roughening treatment includes copper ions and sulfuric acid; The curing liquid used in the curing treatment includes copper ions and sulfuric acid; The total content of soluble sulfate in the alloying solution used for the alloying treatment is 30-100 g / L, and the content of the complexing agent is 20-120 g / L; the soluble sulfate in the alloying solution includes nickel sulfate; the content of nickel ions in the surface coating of the high corrosion-resistant rolled copper foil is 1500-2000 μg / dm 2 ; The anti-oxidation liquid used in the anti-oxidation treatment includes chromium ions, zinc ions and potassium pyrophosphate; The passivation agent used in the passivation treatment is a coupling agent solution.
2. The surface treatment method according to claim 1, characterized in that: The alloying treatment temperature is 25-30°C, and the current density is 5-15A / dm 2 , pH value is 8-10, and electroplating time is 3-5s.
3. The surface treatment method according to claim 1, characterized in that: The soluble sulfate in the alloying solution further comprises one or more of copper sulfate, titanium sulfate and cerium sulfate.
4. The surface treatment method according to claim 1, characterized in that: The complexing agent is an organic substance with carboxyl and / or amino groups.
5. The surface treatment method according to claim 1 or 4, characterized in that: The complexing agent includes one or more of glycolic acid, citric acid, ammonium citrate, thiourea, glycine, phenylalanine, glutamic acid, histidine and alanine.
6. The surface treatment method according to claim 1, characterized in that: The concentration of copper ions in the roughening solution used in the roughening treatment is 5-15 g / L, and the concentration of sulfuric acid is 80-130 g / L; the temperature of the roughening treatment is 25-35°C, and the current density is 18-30 A / dm 2 , the electroplating time is 5 to 10 seconds.
7. The surface treatment method according to claim 1, characterized in that: The concentration of copper ions in the curing liquid used for the curing treatment is 20-60 g / L, and the concentration of sulfuric acid is 80-130 g / L; the temperature of the curing treatment is 25-35°C, and the current density is 10-15 A / dm 2 , the electroplating time is 3 to 6s.
8. The surface treatment method according to claim 1, characterized in that: The concentration of chromium ions in the anti-oxidation liquid used for the anti-oxidation treatment is 0.5-1 g / L, the concentration of zinc ions is 2-4 g / L, and the concentration of potassium pyrophosphate is 100-200 g / L; the pH value of the anti-oxidation liquid is 11-12; the temperature of the anti-oxidation treatment is 20-30° C., and the current density is 2-10 A / dm 2 , the processing time is 5 to 10 seconds; The passivation treatment is to spray a coupling agent solution onto the surface of the rolled copper foil after the anti-oxidation treatment; the volume concentration of the coupling agent solution is 1-2%.
9. A highly corrosion-resistant rolled copper foil, characterized in that: The copper foil is obtained by subjecting a rolled copper foil to surface treatment, wherein the surface treatment method is the surface treatment method according to any one of claims 1 to 8.
10. Use of the highly corrosion-resistant rolled copper foil according to claim 9 in the preparation of fine line width printed circuit boards; the line width of the fine line width printed circuit boards is less than 50 μm.
Citation Information
Cited By
Rolled copper foil for current collector of lithium ion battery and preparation method of rolled copper foil
CN120989614A